Customs and excise trade, production and consumption in England 1640-1845 - Ashworth, William J. (Oxford University Press, 2003)
In this text, the author traces the growth of customs and excise, their integral role in shaping the framework of industrial England, and their influence on elements such as state power, technical advance, and the evolution of a consumer society.